2018
DOI: 10.1136/bmjoq-2017-000222
|View full text |Cite
|
Sign up to set email alerts
|

Focused educational intervention improves but may not sustain knowledge regarding falls management

Abstract: BackgroundThe number of falls in hospital ranges from 3.8 to 8.6 falls per 1000 bed days. 1 Around 30% of falls as inpatients are injurious, and 4%–6% can result in serious and life-threatening injury. 2 3 This results in significant health burdens and economic burdens due to increased hospital stays following a fall. Junior doctors are usually the first point of contact for managing patients who fall in hospital. It is therefore important they understand the preventative measures and postfalls management.Ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
1
12
0
1
Order By: Relevance
“…Four studies reported using trained interventionists to deliver the education, including change agents and falls ‘champions’ [ 44 , 45 , 71 , 79 ]. Research team members (including project representatives) were the educators in around one-quarter [ 43 , 46 , 48 , 51 , 52 , 54 , 64 , 68 , 69 , 76 ]. Geriatrician clinical educators were the educators in two studies [ 67 , 73 ], and where the study was carried out in a simulation centre, the simulation centre staff were the educators [ 60 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies reported using trained interventionists to deliver the education, including change agents and falls ‘champions’ [ 44 , 45 , 71 , 79 ]. Research team members (including project representatives) were the educators in around one-quarter [ 43 , 46 , 48 , 51 , 52 , 54 , 64 , 68 , 69 , 76 ]. Geriatrician clinical educators were the educators in two studies [ 67 , 73 ], and where the study was carried out in a simulation centre, the simulation centre staff were the educators [ 60 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the figures cited above, it is apparent that 2018 shows a further increase in the number of articles citing the Pyramid. In the brief time that this paper was under review, at least six new medical education articles citing the Pyramid and its variations were published, ensuring that 2018 will be well represented in entrenching this myth.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly relevant where DRUJ congruity is being assessed and specifically when comparing studies which may have been obtained in different positions. 13 Previous studies have examined the use of educational interventions to improve compliance with clinical practice standards, [29][30][31][32] particularly medication administration errors, 33 although radiography examples are limited. 34,35 It is recognised that quality assurance processes are used within imaging departments and improvement strategies are employed, but these appear to be focussed at a local level.…”
Section: Discussionmentioning
confidence: 99%
“…Lecture-based education has limitations, including poor retention of information, in addition to challenges of attendance and delivery patterns. 29 As educational posters also are available over an extended period of time, it was also hoped that it could serve as a reminder for staff, supporting retention of knowledge. Although the overall improvement was initially significant, the impact was seen to vary across hospital sites; however, the reason for this was not investigated further.…”
Section: Discussionmentioning
confidence: 99%